Effect of surface texturing on hydrodynamic performance of journal bearings - Hamdavi, S. (Asian Research Publishing Network, 2016)
The request to use hydrodynamic journal bearings in different industries consisting high speed and high load are commonly demanded. The necessary of improving its performance is a significant objective. In this paper, the effect of partially textured surface of hydrodynamic long journal bearing on the pressure distribution and load carrying capacity was studied. Based on governing Reynolds equation, the equations of pressure distribution and load carrying capacity were derived and their trends were represented. The results show that, applying partial surface texture had a positive and remarkable effect on functional characteristics of hydrodynamic journal bearings, i.e. load carrying capacity and lubricant film pressure. Â© 2006-2016 Asian Research Publishing Network (ARPN).